Contrasting nutrient-capture strategies in shrubs and grasses of a Patagonian arid ecosystem - Sala, Osvaldo Esteban (2012)
Shallow-rooted grasses and deep-rooted shrubs dominate arid ecosystems where nitrogen is concentrated in the upper layers of the soil and water is distributed throughout. Analysis of mineral nitrogen and absorption patterns using a tracer indicated that shrubs in Patagonia absorbed nutrients from the lower, relatively nutrient-poor layers of the soil. Are they, consequently, at a competitive disadvantage with grasses that have the opposite pattern? Studies of nitrogen economy indicated that shrub and grass species have similar N-use efficiency but that they achieve it through opposite mechanisms. Shrubs have a conservative N economy absorbing annually only small fraction of their N content, whereas grasses have a more open N economy. This study about N-capture strategies in conjunction with previous studies about water-use by shrubs and grasses in the Patagonian Steppe suggest a coupling of N and watercapture strategies. Our findings have implications for the response of arid and semiarid ecosystems to global warming, nitrogen deposition, and biodiversity change. For example, climate change scenarios predict, for most arid regions, decreases in moisture availability that will result in a reduction in deep water, which in turn will reduce shrub density and result in a less conservative nitrogen economy.